2012
DOI: 10.1186/1472-6947-12-104
|View full text |Cite
|
Sign up to set email alerts
|

Health numeracy in Japan: measures of basic numeracy account for framing bias in a highly numerate population

Abstract: BackgroundHealth numeracy is an important factor in how well people make decisions based on medical risk information. However, in many countries, including Japan, numeracy studies have been limited.MethodsTo fill this gap, we evaluated health numeracy levels in a sample of Japanese adults by translating two well-known scales that objectively measure basic understanding of math and probability: the 3-item numeracy scale developed by Schwartz and colleagues (the Schwartz scale) and its expanded version, the 11-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Third, although it has been used and validated in previous studies, 15,25 our only measure of health literacy was a self-administered instrument. Skill-based measures of health literacy and numeracy such as the Newest Vital Sign 26 and the Lipkus scale 27 have recently been translated and validated in Japanese, and should be also used in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although it has been used and validated in previous studies, 15,25 our only measure of health literacy was a self-administered instrument. Skill-based measures of health literacy and numeracy such as the Newest Vital Sign 26 and the Lipkus scale 27 have recently been translated and validated in Japanese, and should be also used in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite initial reports, descriptive statistics for the Subjective Numeracy Scale (M = 4.19, SD = .85, Cronbach's α = .79), Abbreviated Numeracy Scale (M = 4.04, SD = 1.58, Cronbach's α = .54), and Graph Literacy Scale (M = 10.79, SD = 1.45, Cronbach's α = .40) revealed that two of the three scales did not reach minimum acceptable reliability for the sample used in this study. Nevertheless, previous studies have demonstrated relationships with the numeracy scale despite issues with internal consistency (e.g., Bruine de Bruin, McNair, Taylor, Summers, & Strough, 2014;Nelson, Reyna, Fagerlin, Lipkus, & Peters, 2008;Okamoto et al, 2012). Studies using the Graph Literacy Scale have predominantly reported only the reliability from the original study, so it is unclear whether internal consistency has been an issue in other studies.…”
Section: Numeracy and Graph Literacymentioning
confidence: 99%
“…The concept of HL has recently begun to attract notice in Japan, where nearly 100 % of the population over the age of 15 can read and write the Japanese language. There have been some attempts to develop self-rated scales for measuring HL in Japanese speakers [8][9][10][11][12]. One of these, developed by Ishikawa and colleagues [8], has the advantage of dealing with all three levels of HL: (1) functional literacy-sufficient basic skills in reading and writing to be able to function effectively in everyday situations, a definition which is broadly compatible with the narrow definition of HL; (2) communicative literacy-more advanced skills to participate actively in everyday activities, to extract information and derive meaning from different forms of communication, and to apply new information to changing circumstances; (3) critical literacy-more advanced skills to analyze information critically and to use this information to exert greater control over life events and situations [13].…”
Section: Introductionmentioning
confidence: 99%